FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MENONTON FILM DI BIOSKOP (Studi pada Penonton Bioskop Yogyakarta) - Akhmad Rajabiyanor; Ida Bagus Nyoman Udayana; Bernadetta Diansepti Maharani (JURNAL CAFETARIA, 2022)
The purpose of the study was to determine the effect of business location factors, price feasibility, and word of mouth on consumer decisions to watch in the cinema. This research is a quantitative research. Data collection techniques using a questionnaire. The data analysis technique used descriptive statistical analysis, the classical assumption test consisted of normality, multicollinearity, and heteroscedasticity tests, and multiple regression tests. The results of the study show that (1) the location of the business has a positive effect on the decision to watch the cinema in Yogyakarta with a tcount = 2,985 with a p-value = 0.004 <0.05. (2) The feasibility of the price has a positive effect on the decision to watch the cinema in Yogyakarta with a value of tcount = 3,456 with a p-value = 0.001 <0.05. (3) Word of mouth has a positive effect on consumer decisions in cinemas in Yogyakarta with tcount = 3.277 with p-value = 0.001 <0.05. (4) There is a simultaneous influence of business location, price feasibility, and word of mouth have a positive effect on the decision to watch the cinema in Yogyakarta with a value of Freg = 79.970 with a p value (significance) of 0.000.